2010
DOI: 10.1016/j.crohns.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

OCTN1 variant L503F is associated with familial and sporadic inflammatory bowel disease

Abstract: The present results replicated the association of the OCTN1 rs1050152 (L503F) variant with CD and IBD overall. A weak gender-specific effect of rs1050152 (L503F) on male UC and female CD was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…In addition, they found that the haplotype consisting of L503F of OCTN1 and g.-207G>C of OCTN2 was significantly associated with susceptibility to Crohn's disease. This finding was validated in subsequent studies [9,10,11,12,13,14]. …”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, they found that the haplotype consisting of L503F of OCTN1 and g.-207G>C of OCTN2 was significantly associated with susceptibility to Crohn's disease. This finding was validated in subsequent studies [9,10,11,12,13,14]. …”
Section: Introductionsupporting
confidence: 73%
“…Many previous studies reported that a missense variant of OCTN1 is associated with the susceptibility to, or progression of, human diseases, particularly Crohn's disease [8,9,10,11,12,13,14,15]. For example, Peltekova et al [8] demonstrated that L503F of OCTN1 showed increased transport activity for TEA while it had decreased transport activity for other endogenous compounds including carnitine through in vitro uptake assay.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the gene cluster that contains the OCTN1 and OCTN2 genes have been associated with autoimmune diseases. OCTN1 variant L503F is associated with familial and sporadic inflammatory bowel disease (Lin et al ., 2010). Functionally, this variant has altered substrate specificity with a significantly increased affinity for the common model substrate TEA (Urban et al ., 2007).…”
Section: Octsmentioning
confidence: 99%
“…65,66 Polymorphisms in SLC22A5, which encodes OCTN2 the carnitine transporter involved in mitochondrial FAO, are associated with CD risk. 67 Deletion of OCTN2 in mice caused spontaneous colitis. 68 Mice deficient in PGC1α, a master regulator of mitochondrial biogenesis, exhibited exacerbated intestinal inflammation associated with decreased mtDNA levels.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%